2019
DOI: 10.1002/app.48286
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐impregnated natural zeolite as filler in mixed matrix membranes for CO2/CH4 separation

Abstract: Flat mixed matrix membranes (MMMs) comprising polysulfone and clinoptilolite-type natural zeolite were prepared by casting. Zeolite was modified with three alkylamines: ethanolamine (EA), bis(2-hydroxypropyl)amine (BHPA), and polyethylenimine (PEI) by the impregnation method. Impregnated zeolite samples were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and N 2 adsorption-desorption. The alkylamine loading extent determined by thermogravimetric analysis was 5.2, 4.8, and 8.5% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Mixed-gas permeability tests were performed with a customized permeation apparatus reported elsewhere, and following the same procedure. 32 Flat polymeric and MMMs (5 cm-diameter, 70-100 μmthickness, 5.06 cm 2 effective area tested) were placed onto a ceramic support (porosity: 3 μm, thickness 6 mm) between two-chamber cell. Helium (99.999%) was used for the baseline and as carrier gas.…”
Section: Gas Permeability Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed-gas permeability tests were performed with a customized permeation apparatus reported elsewhere, and following the same procedure. 32 Flat polymeric and MMMs (5 cm-diameter, 70-100 μmthickness, 5.06 cm 2 effective area tested) were placed onto a ceramic support (porosity: 3 μm, thickness 6 mm) between two-chamber cell. Helium (99.999%) was used for the baseline and as carrier gas.…”
Section: Gas Permeability Testsmentioning
confidence: 99%
“…For example, in a previous work of our research group, the incorporation of 10 wt% natural zeolite modified with different alkylamines had beneficial effects on the CO 2 /CH 4 mixed‐gas transport parameters of polysulfone‐based MMMs. Here, the enhancement up to 55% on selectivity and a little significant variation of CO 2 permeability could be accomplished by adding zeolite impregnated with a secondary hydroxyalkyl amine, in comparison with the pristine membrane 32 . In a similar context, Suhail et al 33 recently reported MMMs based on polysulfone and mesoporous SBA‐16 functionalized with pyrazole group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability system was previously described and reported. [28][29] The upstream side was pressurized to 50, 150, and 300 psi of feed gas mixture with a solenoid valve and determined with equipment pressure detector, additionally, has a downstream section with a pressure detector. This section was at atmospheric pressure (14.7 psi) using Helium as carrier gas.…”
Section: Permeation Measurements Of Binary (N 2 /Ch 4 ) and Ternarymentioning
confidence: 99%
“…[10][11][12][13] In recent years, polymeric membranes have received specific attention in the CO 2 separation applications, and in particular, rubbery polymers are more attractive due to their flexible chains allow the chain segments to rotate freely around the main chain bounds. [14][15][16] Low et al 17 indicated that rubbery polymers based on poly (ethylene oxide) (PEO) or poly (ethylene glycol) (PEG) emerge as promising candidates for the CO 2 separation membranes. The CO 2 selective PEO gas separation membranes have high CO 2 solubility by the ether oxygen group of the main chain based on Lewis acid-base interaction between ether oxygen (Lewis base) and CO 2 (Lewis acid).…”
Section: Introductionmentioning
confidence: 99%